EXAMINATION OF INFLUENCE OF ORGANISATIONAL FRUSTRATION ON JOB SATISFACTION AMONG NIGERIAN ARMY PERSONNEL - Balogun, Emmanuel Yusuf; Osa-Afiana, Damian D.; Fashola, Timileyin M. (African Journal of Social and Behavioural Sciences, 2024)
The study investigated the influence of organizational frustration on job satisfaction among Nigerian Army personnel. The study adopted a cross-sectional research design and gathered data from 238 Army personnel in 8 divisions of the Nigerian Army, namely Kaduna, Ibadan, Jos, Port Harcourt, Bornu, Sokoto, Lagos, and Enugu. Data was gathered using the 20-item Minnesota Job Satisfaction and 29-item Job Frustration scales. The data was analyzed using Pearson r correlation and linear regression analysis. The average age of respondents was 34.54 (SD = 12.09), while the majority of them, 92.9%, were males. Findings revealed that there exists a significant relationship between job frustration and job satisfaction (r = -.56; p <.01). Also, it was identified that job frustration had a significant influence on job satisfaction among Nigerian Army personnel (β =.43; t = 6.43, p <.01). Job frustration was found to account for about 31% of the variance in job satisfaction among Nigerian Army personnel. The direction of the beta value (β =.43) further revealed that the higher the job frustration level of the Nigerian Army personnel, the lower their level of job satisfaction. It was recommended that the Nigerian Army carry out periodic assessments of what acts as job satisfaction for their officers. This can be systematically done by assessing what they identify as frustrating in discharging their daily duties.